Performance and degradation of sliding steel friction connections: Impact of velocity, corrosion coating and shim material. (15th June 2017) - Rodgers, G.W.; Chase, J.G.; Causse, R.; Chanchi, J.; MacRae, G.A.
Highlights: Asymmetric friction connections with different coatings and shims were tested. Menegotto-Pinto model with velocity dependence represents the behavior. Devices with an anti-corrosion coatings generally had negative velocity dependence. The model is generalisable for devices that exhibit similar hysteretic behavior. The model is useful to guide design and use of these devices. Abstract: It has become increasingly necessary to develop systems to decrease the impact of earthquakes by protecting people and mitigating resulting structural and economic damage. The Asymmetrical Friction Connection (AFC) or Sliding Hinge Joint (SHJ) has been intensively tested. It efficiently dissipates energy with almost no damage. However, its nonlinear mechanics have not fully been characterised. In this study, the AFC mechanism is fully modelled and parameterised using non-linear modelling. Menegotto-Pinto models of device behaviour, including added velocity dependence, are validated against a series of experimental tests. These SHJs are modelled for several shim (friction sliding surface) materials, as well as with and without corrosion resistant coatings. The non-linear models developed accurately capture the experimentally observed nonlinear mechanics. The impact of shim material and corrosion coating on resistive force and velocity dependence are quantified. In particular, corrosion coatings create negative velocity dependence from a positive dependence without the coating. The overall modelling approach is suitable for use in a wide range of similar dynamic systems. Thus, the results also validate the overall modelling methods and the approach presented.